2021
DOI: 10.1002/smtd.202101043
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Zinc–Air Battery with High Energy Efficiency and Freezing Tolerance Enabled by DMSO‐Based Organohydrogel Electrolyte

Abstract: With the emergence of various flexible electronics, the flexible zinc–air battery (ZAB) is considered a promising energy source with low cost, high energy density, and safety. However, gel electrolytes that improve the freezing tolerance and energy efficiency of ZABs are rarely explored. Herein, an organohydrogel electrolyte (OHE) is fabricated by soaking poly(2‐acrylamido‐2‐methylpropanesulfonic acid)/polyacrylamide (PAMPS/PAAm) double‐network hydrogel in aqueous KOH electrolyte with dimethyl sulfoxide (DMSO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 53 publications
(27 reference statements)
1
47
0
Order By: Relevance
“…NMR spectrum shows no peak of D 2 O, validating that the concentration gradient cannot cause diffusion of D 2 O back to the GPE (Figure S12, Supporting Information).Furthermore, the hydrophilic inner HPβCD can bond strongly with the H 2 O molecules to move the to the right-hand side, mitigating the loss of soluble Zn(OH)4 …”
mentioning
confidence: 82%
See 2 more Smart Citations
“…NMR spectrum shows no peak of D 2 O, validating that the concentration gradient cannot cause diffusion of D 2 O back to the GPE (Figure S12, Supporting Information).Furthermore, the hydrophilic inner HPβCD can bond strongly with the H 2 O molecules to move the to the right-hand side, mitigating the loss of soluble Zn(OH)4 …”
mentioning
confidence: 82%
“…During the charging process, the shape change of Zn anode occurs caused by inhomogeneous and insufficient deposition of reduced Zn because of the loss of Zn(OH) 4 2− . [22] Meanwhile, the preferential deposition of the unreduced Zn(OH) 4 2− at the raised points of Zn surface facilitates the dendrites growth. [23] Noteworthily, the adverse impact…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation
“…7d). Li et al 86 also added DMSO to construct DN poly(2-acrylamido-2-methylpropanesulfonic acid) (PAMPS)/PAM, which exhibited high mechanical strength and good ionic conductivity. Moreover, the introduction of DMSO could change the path of the OER in ZABs and reduce the charge voltage to improve the energy efficiency.…”
Section: Design Strategies For Low-temperature Tolerant Gpes In Zabsmentioning
confidence: 99%
“…Jiang et al reported an organohydrogel electrolyte with excellent mechanical flexibility and high ionic conductivity, which was composed of a dimethyl sulfoxide-added double-network hydrogel soaked with an aqueous KOH electrolyte. A Zn–air battery with this electrolyte exhibited a superior energy density of 523.4 W h kg –1 and a discharge capacity of 562 mA h g –1 at −40 °C . Although the reported hydrogel electrolyte-based Zn–air batteries with organic additives can operate at low temperatures, the water retention, low conductivity, high cost, and other safety risks of the gel electrolyte, such as the flammability and high toxicity of organic additives, remain to be addressed. , Consequently, alkaline aqueous-based electrolytes are still dominating the research at this stage, especially at high concentrations, as the high concentrations of ions reduce the proportion and inhibit the formation of hydrogen bonds .…”
Section: Introductionmentioning
confidence: 99%